Productivity and costs modeling for tree harvesting operations using chainsaws in plantation forests, Tanzania - Silayo, Dos Santos; Migunga, George (International Journal of Engineering and Technology, 2014)
With exemption of a few private forests, timber harvesting in most plantation forests in Tanzania is carried out by less skilled and less equipped crews. Newly recruited crews often learn from experienced ones which may not be doing it in the perfect way. Therefore estimation and projecting production and costs becomes a big problem to logging managers. This study was carried out to develop productivity and costs models for chainsaw operators in a learning experiment. The experiments were designed in clear felling operations. Three experiments were set where each crew category was studied using time study and work sampling techniques that involved studying crews before training, after training and after the break at an interval of three months. Descriptive statistics and modelling was performed for each crews’ performance. Specific crew’s productivity and costs models have been developed reflecting necessary and unnecessary delay times. Assessment of the production costs show that unit costs decreases with increasing productivity in each unit of measurement of the production rate. It is recommended that productivity and costs for two-man crosscut saw operators be studied and modelled since they are also the main cutting tools used in tree cutting in Tanzania.